2018
DOI: 10.1016/j.nano.2018.04.016
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid nanoparticle-based nicotine nanovaccines: Boosting the immunological efficacy by conjugation of potent carrier proteins

Abstract: A series of hybrid nanoparticle-based nicotine nanovaccines (NanoNicVac) were engineered in this work by conjugating potent carrier protein candidates (Keyhole limpet hemocyanin (KLH) multimer, KLH subunit, cross-reactive material 197 (CRM), or tetanus toxoid (TT)) for enhanced immunological efficacy. NanoNicVac with CRM or TT were processed by dendritic cells more efficiently than that with KLH multimer or subunit. NanoNicVac carrying CRM or TT exhibited a significantly higher immunogenicity against nicotine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 47 publications
0
10
0
Order By: Relevance
“…The T cell activation upon incubation of RNase-A or RNase-S with splenocytes harvested from RNase-S vaccinated mice was near zero, however, which seems to indicate that RNase-S failed to reach APCs upon in vivo administration (182). When considering MHC class II pathway, increased antigen complexity has been shown to slow in vitro DC processing and decrease in vivo antibody response (183). For example, So et al observed that the stability of two recombinantly modified hen-egg lysozyme proteins (one with a deleted di-sulfide bond and the other with a selectively added intramolecular ester bond) was inversely correlated with CD4+ T cell activation and both cytokine and antibody production in a mouse model (184).…”
Section: The Impact Of Pbv Stability On Apc Processing and T Cell Actmentioning
confidence: 99%
“…The T cell activation upon incubation of RNase-A or RNase-S with splenocytes harvested from RNase-S vaccinated mice was near zero, however, which seems to indicate that RNase-S failed to reach APCs upon in vivo administration (182). When considering MHC class II pathway, increased antigen complexity has been shown to slow in vitro DC processing and decrease in vivo antibody response (183). For example, So et al observed that the stability of two recombinantly modified hen-egg lysozyme proteins (one with a deleted di-sulfide bond and the other with a selectively added intramolecular ester bond) was inversely correlated with CD4+ T cell activation and both cytokine and antibody production in a mouse model (184).…”
Section: The Impact Of Pbv Stability On Apc Processing and T Cell Actmentioning
confidence: 99%
“…Using these targeting molecules as well as incorporating the nicotine haptens into the core and shell to create a 100 nm particle leads to approximately 60% less nicotine entering the brain than non-nano-mediated vaccines. However, it is unknown if this decrease is sufficient to reduce addictive potential/hedonic value [145][146][147].…”
Section: Nanomedicine For Addiction and Drug Abuse-mentioning
confidence: 99%
“…MHC class II epitopes were chosen for analysis due to their role as facilitators of humoral immune responses via the activation of T H cells. This activation is crucial to antibody production and as such plays an important role in the success of vaccines that are dependent on antibody effector functions, such as vaccines against drugs of abuse [ 29 , 30 ]. Using the output from these predictions, ‘universal’ chimeric antigens (UCAs) were designed that can be used to target mouse models with IAd and/or IEd isotype, and using HLA-DQB1 and HLA-DRB1 allele frequency data, 99% of the US population based on HLA-DQ and HLA-DR isotypes.…”
Section: Introductionmentioning
confidence: 99%